Assessing the Growth of Gifted Students. (January 2013) - McCoach, D. Betsy; Rambo, Karen E.; Welsh, Megan
This Methodological Brief gives an overview of statistical methods used to gauge academic growth and discusses issues surrounding the measurement of growth in gifted populations. To illustrate some of these issues, we describe a growth model that examines differences in summer lag between gifted and nongifted students. We also provide recommendations for educators and researchers who are interested in documenting the academic growth of gifted students.